Photography. - Hogan, Susan (Arts for health., 2022)
Photography is ubiquitous. The visual image is the predominant form of communication. This book explores the myriad ways in which photographs can be used: to document events, places or things; to consolidate personal identity; to pose a challenge to an idea or regime; to animate the inanimate.